The Effect Of Product Quality On Customer Satisfaction At The Fajar Building Shop, Topoyo Sub-District, Mamuju District, West Sulawesi Province - Fadil, M.; Pasigai, Moh Aris; Nurlina, Nurlina (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2025)
The Influence of Product Quality on Customer Satisfaction at Fajar Shop, Building, Topoyo District, Mamuju Regency, West Sulawesi